Restorative justice as a factor of family integration (Revista de Investigaciones Universidad del Quindío, 2021)
The restorative justice system represents a leading role for the parties involved in the conflict, in addition to conceiving community participation and implementing mechanisms that strengthen not only individual but collective well-being. This type of justice is committed to humanization, to create, maintain, and strengthen the social fabric between civil society itself, as well as with the State. One of the advantages of restorative justice is that it escapes the legal sphere as it has a beneficial scope and impact beyond it, such as education, community, as well as family. This document addresses the relationship of restorative justice with family integration, in order to expose the advantage of implementing this mechanism in the daily lives of families and thus lead together a society with a culture of peace.
Keywords: conflict; coexistence; culture of peace; restorative processes; family